Preparation of Physical Education Teachers in 1920-s in Ukraine - Koval’chuk, Hennadiy (Pedagogical Discourse, 2013)
The paper presents the content, forms and methods of general and special methodical preparation of future teachers of physical education in 1920-s in Ukraine due to acute shortage of specialists in physical education. The author illustrates the process of restructuring and new forms of athletic training staff, which was carried out in a training course at the department and the Faculty of Physical Education at the Institute of Education through seminars and certification the study of scientific and methodological expertise in the formation of human resources, the possibilities of using achievements this period in modern terms.